LOW TEMPERATURE SYNTHESIS AND CHARACTERIZATION OF LA2NIMNO6 NANOPARTICLES - P. S. R. Murthy, Ciano Fernandes, Shubham Gaonkar, Samruddhi Azrekar, Apoorba Singh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Abstract The synthesis, structure and characterization of La2NiMnO6 nanoparticles were studied using a simple sol-gel combustion method at 600°C. The overall process involves three steps – formation of homogenous solution, formation of dried gel and final combustion of the dried gel. On ignition in air, the compound is found to transform into nanosized La2NiMnO6 nanoparticles. The analysis of X-ray diffraction (XRD) data confirmed the monoclinic La2NiMnO6 perovskite of space group P21/n without any impurity phase. The Scherrer’s formula was employed to estimate the crystallite size of the prepared sample. For a further insight into the crystal structure, Scanning electron microscopy (SEM) imaging was done. The estimated values of the crystallite size from Scherrer’s formula and SEM were found to be roughly the same. The SEM images confirmed the polycrystalline nature of the prepared sample. Furthermore, UV measurements were performed on the compound to estimate its band gap energy. The values were found to match well with those reported elsewhere in literature. EDX measurements performed on the sample confirmed the existence of La, Ni, Mn and O elements.